The Substantial Characteristics of Organizational and Pedagogical Conditions of Future Primary School Teachers’ Professional Self-Development - Smoliuk, Artem (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article presents reasonably organizational and pedagogical conditions of professional self-development of primary school teachers, namely: support of positive motivation of achievement as meeting internal needs of the individual in professional self-development; the use of cognitive and informative opportunities of the content psychological and pedagogical and methodical disciplines for the formation of didactic complex and technological knowledge and skills, abilities to integrate spatial and substantive, informative and motivational, psychological, social and communication components of the educational environment of teachers’ training college; creating rich social and communicative space in the course of interactive cooperation of learning subjects to create students’ “success situations” and demonstrating positive experience of the professional success. The result of these organizational and pedagogical conditions of the professional self-development of primary school teachers have reflexive-value treatment to the personality as a future teacher and professional considering his or her strengths and weaknesses, formed a high level of readiness for professional self-development in his or her chosen profession